Cryoballoon or Radiofrequency Ablation for Atrial Fibrillation Assessed by Continuous Monitoring: A Randomized Clinical Trial. Issue 22 (26th November 2019) - Andrade, Jason G.; Champagne, Jean; Dubuc, Marc; Deyell, Marc W.; Verma, Atul; Macle, Laurent; Leong-Sit, Peter; Novak, Paul; Badra-Verdu, Mariano; Sapp, John; Mangat, Iqwal; Khoo, Clarence; et al.
Abstract : Background: Advanced generation ablation technologies have been developed to achieve more effective pulmonary vein isolation (PVI) and minimize arrhythmia recurrence after atrial fibrillation (AF) ablation. Methods: We randomly assigned 346 patients with drug-refractory paroxysmal AF to contact force–guided radiofrequency ablation (CF-RF; n=115), 4-minute cryoballoon ablation (Cryo-4; n=115), or 2-minute cryoballoon ablation (Cryo-2; n=116). Follow-up was 12 months. The primary outcome was time to first documented recurrence of symptomatic or asymptomatic atrial tachyarrhythmia (AF, atrial flutter, or atrial tachycardia) between days 91 and 365 after ablation or a repeat ablation procedure at any time. Secondary end points included freedom from symptomatic arrhythmia and AF burden. All patients received an implantable loop recorder. Results: One-year freedom from atrial tachyarrhythmia defined by continuous rhythm monitoring was 53.9%, 52.2%, and 51.7% with CF-RF, Cryo-4, and Cryo-2, respectively ( P =0.87). One-year freedom from symptomatic atrial tachyarrhythmia defined by continuous rhythm monitoring was 79.1%, 78.2%, and 73.3% with CF-RF, Cryo-4, and Cryo-2, respectively ( P =0.26). Compared with the monitoring period before ablation, AF burden was reduced by a median of 99.3% (interquartile range, 67.8%–100.0%) with CF-RF, 99.9% (interquartile range, 65.3%–100.0%) with Cryo-4, and 98.4% (interquartile range, 56.2%–100.0%) with Cryo-2 ( P =0.36). Serious adverse events occurred in 3 patients (2.6%) in the CF-RF group, 6 patients (5.3%) in the Cryo-4 group, and 7 patients (6.0%) in the Cryo-2 group, with no significant difference between groups ( P =0.24). The CF-RF group had a significantly longer procedure duration but significantly shorter fluoroscopy exposure ( P <0.001 vs cryoballoon groups). Conclusions: In this multicenter, randomized, single-blinded trial, CF-RF and 2 different regimens of cryoballoon ablation resulted in no difference in 1-year efficacy, which was 53% by time to first recurrence but >98% burden reduction as assessed by continuous cardiac rhythm monitoring. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01913522. Abstract : Supplemental Digital Content is available in the text.